1993
DOI: 10.1111/j.1526-4610.1993.hed3307365.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Symptoms In Patients With Posttraumatic Headache

Abstract: A variety of symptoms (postconcussion symptoms) have been consistently reported following mild head or neck injury. One symptom which may have been under reported is cognitive impairment. We conducted a retrospective study of 100 patients presenting for evaluation and treatment of posttraumatic headache at our headache clinic. Sixty-five percent reported difficulties with either memory, concentration, and/or thinking. The most common cognitive symptoms reported were concentration+memory problems, concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 10 publications
3
19
0
1
Order By: Relevance
“…It is generally thought that in the acute phase of post‐traumatic headache the associated organic changes account for the majority of symptoms, while the longer the pain prevails, the more psychosocial and psychological factors come into play 51 . Packard et al reported that 65% self‐report deficits in memory, concentration, and thinking 52 . Gfeller et al reported similar deficits in memory and concentration, but found that those patients scoring high on self‐report end up with greater deficits on formal objective neuropsychological testing 53 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…It is generally thought that in the acute phase of post‐traumatic headache the associated organic changes account for the majority of symptoms, while the longer the pain prevails, the more psychosocial and psychological factors come into play 51 . Packard et al reported that 65% self‐report deficits in memory, concentration, and thinking 52 . Gfeller et al reported similar deficits in memory and concentration, but found that those patients scoring high on self‐report end up with greater deficits on formal objective neuropsychological testing 53 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…Other demographic factors such as the level of education (Keyser-Marcus et al, 2002), early post-injury cognitive status (Sherer et al), and the presence of chronic pain (Lahz & Bryant, 1996) have also been found to impact MTBI recovery. With the exception of chronic pain (Carroll et al, 2004;Gfeller, Gripshover, & Chibnall, 1996;Iverson & McCracken, 1997;Packard, Weaver, & Ham, 1993;Smith-Seemiller, Fow, Kant, & Franzen, 2003) and to a lesser extent gender (Santa Maria, Pinkston, Miller, & Gouvier, 2001), which have been shown to be related to the endorsement of PCS-like symptoms, whether these other factors are directly associated with PCS-symptom endorsement in the absence of MTBI has yet to be clearly determined.…”
mentioning
confidence: 97%
“…General findings indicate a range of deficits including diminished rates of information processing, impaired problem‐solving ability, mental fatigue, and disturbance of long‐term and verbal memory 26 . In a study by Packard et al, 65 of 100 patients had cognitive difficulties, with problems or deficits in memory and concentration rated as the most prominent symptoms 27 …”
mentioning
confidence: 99%